Keterampilan Berpikir Kritis Dalam Pembelajaran Ilmu Pengetahuan Sosial - Tri Ulfa; Erni Munastiwi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This study aims to determine at critical thinking skills at the elementary school (SD) in Industrial Revolution 4.0. The focus lies on the critical thinking skills of students in Social Sciences (IPS) subjects. The research was conducted by means of literature review related to critical thinking of learning Social Sciences (IPS) for the elementary school level (SD / MI). Sources of data are collected through scientific journals, books, or final projects and analyzed descriptively qualitatively. Results obtained from children coping with problems with reciprocal interactions in an educational setting. Social Sciences (IPS) is a combination of social sciences and humanities. Learning Social Sciences (IPS) at the SD / MI level is carried out with an interdisciplinary approach. Thus, it can be denied that learning Social Sciences (IPS) at the elementary school level (SD / MI) makes students develop into individuals who are easily adaptable and support students critical thinking patterns so that they can coexist with both local and global communities.